2014
DOI: 10.1021/la503399x
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Effects on Kinetic Mechanisms of Self-Assembly by Peptide Amphiphiles via Molecular Dynamics Simulations

Abstract: Peptide amphiphiles are known to form a variety of distinctive self-assembled nanostructures (including cylindrical nanofibers in hydrogels) dependent upon the solvent conditions. Using a novel coarse-grained model, large-scale molecular dynamics simulations are performed on a system of 800 peptide amphiphiles (sequence, palmitoyl-Val3Ala3Glu3) to elucidate kinetic mechanisms of molecular assembly as a function of the solvent conditions. The assembly process is found to occur via a multistep process with trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 71 publications
(153 reference statements)
2
50
0
1
Order By: Relevance
“…Similarly, a study utilizing the ePRIME force field 24 to CG PAs reported a spherical micelle to rod shape nanostructure transformation. 27 Within this study, with increasing hydrophobicity strength as low, moderate and high, three clusters were observed—random clusters, cylindrical nanofibers and elongated micelles.…”
Section: Simulations Of Peptide-amphiphile Self-assembliesmentioning
confidence: 59%
See 3 more Smart Citations
“…Similarly, a study utilizing the ePRIME force field 24 to CG PAs reported a spherical micelle to rod shape nanostructure transformation. 27 Within this study, with increasing hydrophobicity strength as low, moderate and high, three clusters were observed—random clusters, cylindrical nanofibers and elongated micelles.…”
Section: Simulations Of Peptide-amphiphile Self-assembliesmentioning
confidence: 59%
“…With increasing hydrophobicity, first spherical micelles form which later merge to form cylindrical nanofibers and elongated micelles. Adapted with permission from ref 27. Copyright (2015) American Chemical Society.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…The assembly was found to occur via a multistep process with transient intermediates ultimately leading to stable nanostructures. Different kinetic mechanisms were compared on the basis of solvent-accessible surface area, radius of gyration, relative shape anisotropy, intra/intermolecular interaction, and aggregate size (Fu et al, 2015). Comparatively, only few simulation studies have been reported on the loading/release of drugs in amphiphilic peptides.…”
Section: F4h5k15 F8h5k15 F12h5k15 F16h5k15mentioning
confidence: 99%